Fuzzy Logic-Enhanced Direct Power Control for Wind Turbines with Doubly Fed Induction Generators - Karim Fathi sayeh; Salah tamalouzt; Djamel ZIANE; Brahim Deffaf; Sofia Lalouni BELAID; Youcef BELKHIER; Mohit BAJAJ; Vojtech BLAZEK (Results in Engineering)
ABSTRACT: This paper introduces a novel approach, F12-DPC (Fuzzy Logic-based 12-sector Direct Power Control), aimed at significantly improving the performance of wind turbines using Doubly Fed Induction Generators (DFIGs). This innovative method overcomes the limitations of traditional Direct Power Control (DPC) by incorporating fuzzy logic to mitigate power fluctuations and reduce total harmonic distortion (THD) in grid currents. The novelty of F12-DPC lies in its ability to precisely control both active and local compensated reactive powers, optimizing energy exchange with the AC grid across various operational modes. Extensive simulations under different wind conditions demonstrate the superiority of F12-DPC over conventional DPC (C-DPC) techniques. It reduces active power variations by up to 72.7% and reactive power variations by 79.2%, while significantly lowering grid current THD—from 6.26% to 1.47% in super-synchronous mode, 6.42% to 2.09% in synchronous mode, and 8.74% to 2.15% in sub-synchronous mode. The simplicity and robustness of F12-DPC make it a breakthrough solution for enhancing wind energy conversion system efficiency and promoting seamless grid integration.